Consumer responses to diverse digital goods: the role of psychological ownership in life planning apps, music streaming services, and game skins: Psychological ownership and digital goods - Kučinskas, Gedas (Journal of Industrial Engineering & Management Research, 2024)
Digital goods have significantly transformed industries and consumer behavior, with Life Planning Apps, Music Streaming Services, and Game Skins becoming integral to daily life. The study aims to explore consumers’ psychological ownership of diverse digital goods and its impact on willingness to pay and purchase intentions. It examines differences in perceived value, anticipated enjoyment, and relevance across various digital products. A survey was conducted with 138 participants recruited via MTurk, who were presented with scenarios for each type of digital product. Participants’ responses were measured using a 7-point Likert scale to evaluate various consumer behavior aspects. Data were analyzed using repeated measures ANOVA and regression analyses. The results show notable differences in consumer perceptions and intentions among the three categories of digital goods. Music streaming services are perceived as culturally integrated and highly valued, leading to strong consumer engagement. Life planning apps evoke a high sense of personal ownership due to their deep integration into users’ daily routines, resulting in high perceived value and relevance. In contrast, game skins are seen as less essential, reflecting lower levels of psychological ownership and perceived value. The study concludes that psychological ownership significantly impacts consumers’ willingness to pay, purchase intentions, anticipated enjoyment, and perceived value across all types of digital goods. These findings highlight the critical role of psychological ownership in digital marketing strategies, suggesting that enhancing consumers’ sense of ownership can improve engagement and satisfaction with digital products.